PHILOSOPHICAL AND RELIGIOUS INTERPRETATIONS OF CONCEPTS OF "DEVELOPMENT" AND "GOAL" OF HUMAN - Конотоп, Л. Г. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Introduction. In the article, the problem of the integrity of man is revealed as a key issue in all anthropological problems. Research methods. The problem the article is devoted to requires the use of new methodological means of cognition that is understood by philosophers, religious scholars and psychologists of the XXI century. Such an approach is very relevant for modern Ukraine, as the upbringing of the younger generation implies awareness and disclosure of the concepts of "becoming" and "integrity". Discussion. Many Foreign and Ukrainian scholars have devoted a sufficient number of jobs to this problem, but some use a reduction method, which leads to one-sided comprehension of the human problem. Research results. Such an approach to the understanding of the integrity of a person gives incomplete understanding of such important issues as the nature of man. Even in the days of Antiquity, spiritual practices, including philosophical ones, had a religious and moral-practical character. The soul was a kind of guarantor of unity and a source of human integrity, which was still potentially. The isolation of the "self" of man through ritual spiritual, practical and rational-theoretical actions leads to the acquisition of integrity, first of all, through the knowledge of man himself. In the Middle Ages, the paradigm of transcendence was dominant. The development of the paradigm of immanence is typical of the Renaissance, when the spiritual practices of "deification" are gradually replaced by intellectual practices. Conclusions. The author substantiates the understanding of the person as a whole ensemble of interconnections as a system. In this regard, the concepts of "becoming" and "integrity" as the main ones in the aspect of the realization of human spirituality, its self-realization, self-identification, are actualized. The multilevel approach to the study of human integrity is realized through the realization of this integrity as the unity of three realities – objective, subjective and transcendental, and the effectiveness of these realities is determined through their manifestations on the basis of three main functions of man – natural, social and spiritual.